2019
DOI: 10.1186/s12909-019-1894-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based education improves student self-efficacy in physiotherapy assessment and management of paediatric patients

Abstract: BackgroundThe Australian Physiotherapy Council mandates that physiotherapy clinical education be sufficient to produce graduates who are competent to practice across the lifespan. Due to a lack of opportunities for paediatric clinical placements, there is a risk of graduates not having the opportunity to develop competency in paediatric physiotherapy. To address this risk, simulation-based education (SBE) has been proposed as an educational strategy to address the placement shortfall. Despite encouraging evide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…Additionally, clinical simulations have demonstrated that students improve 'confidence in clinical skills, clinical decision-making, treatment preparation and planning, communication skills, evaluating and modifying interventions, and interprofessional practice' [26].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, clinical simulations have demonstrated that students improve 'confidence in clinical skills, clinical decision-making, treatment preparation and planning, communication skills, evaluating and modifying interventions, and interprofessional practice' [26].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of educational modalities (e.g., face-to-face, simulation, clinical experiential) and interventions are documented to improve self-efficacy among students (Hough et al, 2019) and clinicians alike (van Dinther et al, 2011). Positive changes in self-efficacy translate to improvements in clinical skill confidence and decision-making, better treatment preparation and planning, more effective communication skills, a better ability to evaluate and modify interventions, and greater preparedness to work with interprofessional partners (Hough et al, 2019).…”
Section: Influence Of Knowledge and Beliefs About Trauma-informed Carementioning
confidence: 99%
“…In Pasupathy and Bogschutz (2013), the act of 'doing' or gaining clinical experience assisted in building students' confidence levels which directly fostered their self-efficacy beliefs. More recently, Hough et al (2019) found that physiotherapy students identified positive changes in their self-efficacy in the assessment and treatment of paediatric cases within a simulation-based education setting. The current study's findings that engagement in academic learning and simulation-based learning activities result in increased comfort and decreased anxiety levels, may provide a unique opportunity to increase speech-language pathologists' comfort in working with people who stutter.…”
Section: Practical Experiences Assist Students To Feel More Comfortable and Less Anxious In Stuttering Managementmentioning
confidence: 99%